Cultivation System and Marketing Chain of Nutmeg in East Seram District, Maluku Province, Indonesia - Kembauw, Esther; Mahulette, Asri Subkhan; Senewe, Rein Estefanus; Wattimena, Anna Yuliana; Kastanya, Agustinus; Lailossa, Anton A.; Wokanubun, Armin Ishak; Samal, Rufaidah (International Journal of Multidisciplinary Sciences and Arts, 2023)
Nutmeg is one of the leading plantation commodities in East Seram Regency, Maluku Province, Indonesia. The nutmeg cultivation system in East Seram Regency is still conventional with an inefficient marketing system. The research aims to obtain data and information on the cultivation system and marketing chain of nutmeg in East Seram District. The research was carried out during the nutmeg harvest season in 2021 using a survey method. The research was conducted in three sub-districts in East Seram District, namely Tutuk Tolu Sub-District (Danama Village), Kian Darat Sub-District (Kileser and Rumfakar Villages), and Bula Barat Sub-District (Dreamland Hills Village). The research was carried out through structured interviews with nutmeg farmers and collectors. Respondents of nutmeg farmers were selected by purposive sampling as many as 20 nutmeg farmers so that there were a total of 80 respondents. The results of the study were informed that the nutmeg cultivation system in East Seram Regency was still conventional, especially in Tutuk Tolu and Kian Darat Districts. Nutmeg farmers have a weak bargaining position in the marketing system because prices are fully determined by collectors